2021
DOI: 10.1097/tp.0000000000003717
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Prophylaxis After Lung Transplantation: Where Are We Now?

Abstract: BackgroundLung transplantation is an important treatment option for various end-stage lung diseases. However, survival remains limited due to graft rejection and infections. Despite that fungal infections are frequent and carry a bad prognosis, there is currently no consensus on efficacy, optimal drug, route or duration of antifungal prophylaxis. This narrative review summarizes current strategies for antifungal prophylaxis after lung transplantation. MethodsEnglish-language articles in Embase, Pubmed, UptoDat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Koutsokera et al [9] published a series of more than 400 pts, where the detection of donor-specific antibodies (DSA) was an early marker associated with the development of graft dysfunction. Some studies have suggested that the presence of pre-transplant HLA antibodies does not impact the risk of development of CLAD and mortality [10]. However, recent literature suggests that pre-transplant HLA antibodies are associated with worse waitlist and post-transplant survival, as well as higher rates of acute cellular rejection and BOS [11].…”
Section: Risk Factors and Causes Of Cladmentioning
confidence: 99%
“…Koutsokera et al [9] published a series of more than 400 pts, where the detection of donor-specific antibodies (DSA) was an early marker associated with the development of graft dysfunction. Some studies have suggested that the presence of pre-transplant HLA antibodies does not impact the risk of development of CLAD and mortality [10]. However, recent literature suggests that pre-transplant HLA antibodies are associated with worse waitlist and post-transplant survival, as well as higher rates of acute cellular rejection and BOS [11].…”
Section: Risk Factors and Causes Of Cladmentioning
confidence: 99%
“…53,54 For lung transplant recipients, the preferred choice between universal or pre-emptive antifungal prophylaxis against Aspergillus (the latter involving routine surveillance with broncho-alveolar lavage culture and galactomannan) is undefined, but either approach is recommended over no prophylaxis. 55,56 Although 90% of US transplant centers had previously reported routine universal antifungal prophylaxis for lung transplant recipients, a review of administrative claims data showed that only 41.5% of patients received antifungal prophylaxis. 57 The reasons for this incongruence is unknown, but further analysis could potentially provide insights to stewardship areas of interest.…”
Section: Antifungal Prophylaxis In Liver and Lung Transplant Recipientsmentioning
confidence: 99%
“…The American Society of Transplantation Infectious Disease Community of Practice recommended 2016 a regimen of NAB for 3–4 months ( 8 ). It has also been suggested that universal antifungal prophylaxis with inhaled amphotericin B and systemic voriconazole for a minimum of 3–6 months following lung transplantation may be beneficial ( 9 ). A Chinese national survey found that invasive pulmonary aspergillosis (IPA) mostly occurs in the first 4–6 months post-transplant ( 3 ).…”
Section: Introductionmentioning
confidence: 99%